Is clopidogrel better than aspirin following breakthrough strokes while on aspirin? A retrospective cohort study - Lee, Meng (BMJ Open, 2014)
OBJECTIVE: There is insufficient evidence on which to base a recommendation for optimal antiplatelet therapy following a stroke while on aspirin. The objective was to compare clopidogrel initiation vs aspirin reinitiation for vascular risk reduction among patients with ischaemic stroke on aspirin at the time of their index stroke. DESIGN: Retrospective. SETTING: We conducted a nationwide cohort study by retrieving all hospitalised patients (≥18 years) with a primary diagnosis of ischaemic stroke between 2003 and 2009 from Taiwan National Health Insurance Research Database. PARTICIPANTS: Among 3862 patients receiving aspirin before the index ischaemic stroke and receiving either aspirin or clopidogrel after index stroke during follow-up period, 1623 were excluded due to a medication possession ratio <80%. Also, 355 were excluded due to history of atrial fibrillation, valvular heart disease or coagulopathy. Therefore, 1884 patients were included in our final analysis. INTERVENTIONS: Patients were categorised into two groups based on whether clopidogrel or aspirin was prescribed during the follow-up period. Follow-up was from time of the index stroke to admission for recurrent stroke or myocardial infarction, death or the end of 2010. PRIMARY AND SECONDARY OUTCOME MEASURES: The primary end point was hospitalisation due to a new-onset major adverse cardiovascular event (MACE: composite of any stroke or myocardial infarction). The leading secondary end point was any recurrent stroke. RESULTS: Compared to aspirin, clopidogrel was associated with a lower occurrence of future MACE (HR=0.54, 95% CI 0.43 to 0.68, p<0.001, number needed to treat: 8) and recurrent stroke (HR=0.54, 95% CI 0.42 to 0.69, p<0.001, number needed to treat: 9) after adjustment of relevant covariates. CONCLUSIONS: Among patients with an ischaemic stroke while taking aspirin, clopidogrel initiation was associated with fewer recurrent vascular events than aspirin reinitiation.